Attenuation correction of dynamic Tc99m-teboroxime myocardial perfusion SPECT - Hsu, B.-L; Case, J.A; Gegen, L.L; Hertenstein, G.K; Cullom, S.J; Bateman, T.M (Journal of nuclear cardiology, 2004)
Background: Tc99m-Teboroxime (TEBO) has been pursued as a myocardial perfusion agent because of its high extraction fraction. However, to image TEBO accurately on traditional SPECT is difficult due to a fast washout rate and the high hepatic uptake. In this work, we develop and demonstrate a new attenuation correction (AC) technique for dynamic SPECT to improve TEBO's perfusion distribution using a novel energy-based listmode scatter correction (SC) combined with AC. Methods: We recruited five subjects having previous clinically indicated rest-stress AC Tc-99m-MIBI SPECT to receive an adenosine stress TEBO. The Gd-153 transmission study was acquired sequentially prior to the TEBO study on Siemens ECAM TM system modified to acquire listmode data in a rapid phased fanning mode. 10s per phase with 32 phases and 32 projection angles in each phase were acquired in 180o RAO-LPO arc during peak adenosine stress. Listmode data were rebinned into energy spectra of projections. The spectrum at each pixel was corrected using a previously reported energy-based SC technique (IESD). Attenuation maps were reconstructed with a Bayesian iterative approach (BITGA) and AC was performed with MLEM algorithm using the IESD corrected projections. Segmental difference from the polar map samplings (total 90 segments) of non-corrected TEBO (NC) TEBO to AC MIBI were compared with AC TEBO to AC MIBI for assessing the improvements of patients' perfusion distribution after AC. Results: The mean segmental difference between NC TEBO and AC MIBI was 7.5 and reduced to 6.0 after AC (p<0.05) as below. Conclusion: AC combined with IESD correction demonstrates improved perfusion distribution of TEBO by reducing 20% (p<0.05) segmental difference of polar maps of NC TEBO. This result indicates that a significant improvement of TEBO's perfusion distribution can be possible if a fast dynamic SPECT and an effective AC+SC method are applied.